2022
DOI: 10.4102/hsag.v27i0.1778
|View full text |Cite
|
Sign up to set email alerts
|

Journey less travelled: Female nursing students’ experiences in providing intimate care in two nursing education institutions in Gauteng province, South Africa

Abstract: This study explored female nursing students' experiences of intimate care for diverse patients.Setting: The study was conducted in two nursing education institutions in Gauteng province, South Africa. Methods:Descriptive phenomenology was used to describe the lived experiences of participants. Seventeen female nursing students were purposively sampled. Data were collected using semi-structured interviews and analysed using Moustakas' (1994) eight steps.Results: Four themes emerged: intimate care comprehension,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…As indicated earlier, intimate care requires a nurse to touch the body of the patient, if it is not facilitated in NEI, the student becomes exposed to the human body during clinical placement. A vast literature from humanistic care scholars such as [9,28,32,33] has indicated that intimate care and touch are not facilitated in skills laboratories and nursing students learn it from trial and error and from other students. Since registered nurses are not knowledgeable about the supervision of intimate care, therefore, intimate care empowerment and support during clinical placement are lacking.…”
Section: Part 1: Discussion Of Phase 2 -Incorporation Of Local Knowledgementioning
confidence: 99%
“…As indicated earlier, intimate care requires a nurse to touch the body of the patient, if it is not facilitated in NEI, the student becomes exposed to the human body during clinical placement. A vast literature from humanistic care scholars such as [9,28,32,33] has indicated that intimate care and touch are not facilitated in skills laboratories and nursing students learn it from trial and error and from other students. Since registered nurses are not knowledgeable about the supervision of intimate care, therefore, intimate care empowerment and support during clinical placement are lacking.…”
Section: Part 1: Discussion Of Phase 2 -Incorporation Of Local Knowledgementioning
confidence: 99%
“…A theory-generative study was conducted, with multiple phases published elsewhere [10,18,20] this manuscript presents descriptive phenomenological experiences of male nursing students in providing intimate care to diverse patients. A phenomenological study focuses on the conscious experiences of the participants and gains meaning from a phenomenon [21].…”
Section: Designmentioning
confidence: 99%